Rectus Pulley Displacements Without Abnormal Oblique Contractility Explain Strabismus in Superior Oblique Palsy - Suh, Soh Youn (Ophthalmology, 2016)
PURPOSE: Using high-resolution magnetic resonance imaging (MRI), we investigated whether rectus pulleys are significantly displaced in superior oblique (SO) palsy, and if displacements account for strabismus patterns. DESIGN: Prospective, case-control study. PARTICIPANTS: Twenty-four patients diagnosed with SO palsy based on atrophy of SO muscle on MRI, and 19 age-matched orthotropic control subjects. METHODS: High resolution, surface coil MRI was obtained in multiple, contiguous, quasicoronal planes during monocular central gaze fixation. Pulley locations in oculocentric coordinates in the following subgroups of patients with SO palsy were compared with normal in subgroups of patients with SO palsy: unilateral vs bilateral, congenital vs acquired, and isotropic (round shape) vs anisotropic (elongated shape) SO atrophy. Expected effects of pulley displacements were modeled using Orbit 1.8® computational simulation. MAIN OUTCOME MEASURES: Rectus pulley positions and ocular torsion. RESULTS: Rectus pulleys were typically displaced in SO palsy. In unilateral SO palsy, on average the medial rectus (MR) pulley was displaced 1.1 mm superiorly, the superior rectus (SR) pulley 0.8 mm temporally, and the inferior rectus (IR) pulley 0.6 mm superior and 0.9 mm nasal from normal. Displacements were similar in bilateral SO palsy, with SR pulley additionally displaced 0.9 mm superiorly. However, the lateral rectus (LR) pulley was not displaced in either unilateral or bilateral SO palsy. The SR and MR pulleys were displaced in congenital SO palsy, while the IR and MR pulleys were displaced in acquired palsy. Pulley positions did not differ between isotropic and anisotropic palsy, or between patients with cyclotropia <7° versus ≥7°. Simulations predicted that the observed pulley displacements alone could cause patterns of incomitant strabismus typical of SO palsy, without requiring any abnormality of SO or inferior oblique strength. CONCLUSION: Rectus pulley displacements alone, without abnormal oblique muscle contractility, can create the clinical patterns of incomitant strabismus in SO palsy. This finding supports accumulating evidence that clinical binocular misalignment patterns are not reliable indicators of contractile function of the SO muscle. Ocular torsion does not correlate with and thus cannot account for pulley displacements in SO palsy.